1997
DOI: 10.1152/ajpcell.1997.273.3.c988
|View full text |Cite
|
Sign up to set email alerts
|

Genistein potentiates wild-type and delta F508-CFTR channel activity

Abstract: Effects of genistein on wild-type (wt) and delta F508-cystic fibrosis transmembrane conductance regulator (CFTR) were studied in NIH/3T3 cells stably transfected with wt or mutant CFTR cDNA. As measured by I- efflux, half-maximal concentration of agonist (K1/2) for forskolin-dependent activation was greater for delta F508-CFTR than wt-CFTR. Genistein decreased the K1/2 for both forms of the channel and increased the maximal activity of delta F508-CFTR by 3.7-fold. In cell-attached patches, 10 microM forskolin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
181
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(192 citation statements)
references
References 26 publications
10
181
1
Order By: Relevance
“…Genistein potentiates cAMP-dependent activation of DF508 CFTR [8]. The present results confirm that genistein induces the cAMP-dependent activation of DF508 CFTR and suggests further that it is able to increase the Cl -secretion achieved after incubation with 4PBA.…”
Section: Discussionsupporting
confidence: 85%
“…Genistein potentiates cAMP-dependent activation of DF508 CFTR [8]. The present results confirm that genistein induces the cAMP-dependent activation of DF508 CFTR and suggests further that it is able to increase the Cl -secretion achieved after incubation with 4PBA.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, the sweat chloride level, a parameter directly reflecting CFTR activity in vivo and thus a widely used diagnostic tool for CF, in patients taking Vx-770 (19,20) were still higher than those found in patients with mild-form CF (19,20,40), suggesting that Vx-770 alone is insufficient to completely rectify the dysfunction associated with the G551D mutation in vivo. Furthermore, recent clinical trials suggest that treatments with drugs that can improve the trafficking of ΔF508-CFTR may not be sufficient to ameliorate the clinical symptoms in patient carrying the ΔF508 mutation (1) presumably because this most common pathogenic mutation causes deficits in both membrane expression and gating (41)(42)(43)(44)(45)(46). Thus, discovering new ways to enhance CFTR activity remains an outstanding goal in the field.…”
Section: Discussionmentioning
confidence: 99%
“…The ⌬F508-CFTR channels exhibit several physiological abnormalities; one of them is the low P o observed in intact cells due to a reduced opening rate (20,22). It was suggested that this low opening rate was due to a very slow phosphorylation rate (30) and not to an intrinsic defect in the gating mechanism.…”
Section: Discussionmentioning
confidence: 99%